Bohemian Rhapsody [videorecording (DVD)] - Malek, Rami; Boynton, Lucy; Lee, Gwilym, 1983- (Twentieth Century Fox Home Entertainment, 2018)
An enthralling celebration of Queen, their music, and their extraordinary lead singer Freddie Mercury, who defied stereotypes and convention to become one of history's most beloved entertainers. Following Queen's meteoric rise, their revolutionary sound and Freddie's solo career, the film also chronicles the band's reunion, and one of the greatest performances in rock history.